Cell surface localised Hsp70 is a cancer specific regulator of clathrin‐independent endocytosis. Issue 19 (6th August 2015) - Nimmervoll, Benedikt; Chtcheglova, Lilia A.; Juhasz, Kata; Cremades, Nunilo; Aprile, Francesco A.; Sonnleitner, Alois; Hinterdorfer, Peter; Vigh, Laszlo; Preiner, Johannes; Balogi, Zsolt
Abstract : The stress inducible heat shock protein 70 (Hsp70) is present specifically on the tumour cell surface yet without a pro‐tumour function revealed. We show here that cell surface localised Hsp70 (sHsp70) supports clathrin‐independent endocytosis (CIE) in melanoma models. Remarkably, ability of Hsp70 to cluster on lipid rafts in vitro correlated with larger nano‐domain sizes of sHsp70 in high sHsp70 expressing cell membranes. Interfering with Hsp70 oligomerisation impaired sHsp70‐mediated facilitation of endocytosis. Altogether our findings suggest that a sub‐fraction of sHsp70 co‐localising with lipid rafts enhances CIE through oligomerisation and clustering. Targeting or utilising this tumour specific mechanism may represent an additional benefit for anti‐cancer therapy. Abstract : The stress inducible heat shock protein 70 (Hsp70) is a tumour cell surface marker. Clustering of cell surface localised Hsp70 (sHsp70) facilitates endocytosis in melanoma cells. sHsp70‐mediated increase in endocytosis may be used in Hsp70 antibody‐based anti‐cancer therapy.